(3WHbGJ GdRjOjIs - (3jMji Hf GdMSjf Hf GdbGSe Hf eMeO, GHf GdbGpSe,J (B1099 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYdeGA ge GdgGOhf GdegJOhf s
(3BNQgG (B:s
(3hgPg GdfSNI GdJi cedJ , heG bHdgG ajgG fbU hJMhjd ai HYV GdehGVY agPg GdeYJeOI hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje (B[ (3hHYO Pdc Pjd GdMbI GdeDda HGdcJGH ai hQbJjf (B] s
(3efbhdg Yf eShOg HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B192s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs